A multipurpose vector system for the screening of libraries in bacteria, insect and mammalian cells and expression in vivo - Laitinen, Olli H. (Oxford University Press, 2005)
We have constructed a novel tetra-promoter vector (pBVboostFG) system that enables screening of gene/cDNA libraries for functional genomic studies. The vector enables an all-in-one strategy for gene expression in mammalian, bacterial and insect cells and is also suitable for direct use in vivo. Virus preparation is based on an improved mini Tn7 transpositional system allowing easy and fast production of recombinant baculoviruses with high diversity and negligible background. Cloning of the desired DNA fragments or libraries is based on the recombination system of bacteriophage lambda. As an example of the utility of the vector, genes or cDNAs of 18 different proteins were cloned into pBVboostFG and expressed in different hosts. As a proof-of-principle of using the vector for library screening, a chromophoric Thr(65)-Tyr-Gly(67)-stretch of enhanced green fluorescent protein was destroyed and subsequently restored by novel PCR strategy and library screening. The pBVboostFG enables screening of genome-wide libraries, thus making it an efficient new platform technology for functional genomics.